Evaluation of clinically relevant states in patient reported outcomes in knee and hip osteoarthritis: the patient acceptable symptom state. Issue 1 (6th May 2004) - Tubach, F; Ravaud, P; Baron, G; Falissard, B; Logeart, I; Bellamy, N; Bombardier, C; Felson, D; Hochberg, M; van der Heijde, D; Dougados, M
Abstract : Background: The patient acceptable symptom state (PASS) is the value beyond which patients can consider themselves well. This concept can help in interpreting results of clinical trials. Objective: To determine the PASS estimate for patients with knee and hip osteoarthritis (OA) by assessing pain, patient's global assessment of disease activity, and functional impairment. Methods: A 4 week prospective multicentre cohort study of 1362 outpatients with knee or hip OA was carried out. Data on assessment of pain and patient's global assessment of disease, measured on visual analogue scales, and functional impairment, measured on the Western Ontario McMaster Universities Osteoarthritis Index (WOMAC) function subscale, were collected at baseline and final visits. The patients assessed their satisfaction with their current state at the final visit. An anchoring method based on the patient's opinion was used. Results: For patients with knee and hip OA, the estimates of PASS were, respectively, 32.3 and 35.0 mm for pain, 32.0 and 34.6 mm for patient global assessment of disease activity, and 31.0 and 34.4 points for WOMAC function score. The PASS varied moderately across the tertiles of baseline scores but not across age, disease duration, or sex. Conclusion: The use of PASS in clinical trials would provide more meaningful results expressed as a proportion of patients in an acceptable symptom state.